International Model for Policy Analysis of Agricultural Commodities and Trade (IMPACT): Model description - Rosegrant, Mark W.; Batka, Miroslav; Bhandary, Prapti; Bryan, Elizabeth; Cenacchi, Nicola; De Pinto, Alessandro; Enahoro, Dolapo; Leroy, Laetitia; Li, Man; Magnan, Nicholas; Mason-D’Croz, Daniel; Msangi, Siwa; et al. (International Food Policy Research Institute, 2012)
The International Model for Policy Analysis of Agricultural Commodities and Trade (IMPACT) was developed at IFPRI at the beginning of the 1990s to address a lack of long-term vision and consensus among policy-makers and researchers about the actions that are necessary to feed the world in the future, reduce poverty, and protect the natural resource base. In 1993, these same long-term global concerns launched the 2020 Vision for Food, Agriculture, and the Environment Initiative which created the opportunity for further development of the IMPACT model. In 1995 the first results using IMPACT were published as a 2020 Vision discussion paper: Global Food Projections to 2020: Implications for Investment (Rosegrant et al. 1995) in which the effects of population, investment, and trade scenarios on food security and nutrition status, especially in developing countries, were analyzed. IMPACT continues to serve as the basis for research examining the linkage between the production of key food commodities and food demand and security at the national level in the context of scenarios of future change. Studies focus on regional issues, commodity-level analyses, and cross-cutting thematic issues. IMPACT is also embedded in a variety of major global assessments to complement interdisciplinary, scenario-based work on the future of food supply and demand. The first comprehensive set of results for IMPACT were published in the book Global Food Projections to 2020 (Rosegrant et al. 2001). These projections—which were presented in 2001 at the IFPRI-sponsored conference in Bonn entitled: Sustainable Food Security for All by 2020—are presented with details on the demand system and other underlying data used in the projections work, and cover both global and regionally-focused projections. A complete list of the research published using the IMPACT modeling framework is provided in Appendix 1, including reports for international organizations, such as the World Bank, the Asian Development Bank, the FAO, and national governments.